PENGARUH KARAKTERISTIK INDIVIDU TERHADAP KINERJA KARYAWAN PADA RUMAH SAKIT UMUM DAERAH BREBES - Rahayu, Sri (PERMANA, 2015)
This study entitled "Individual Characteristics Influence on Employee Performance At the General Hospital of Brebes". Goals to be achieved in this research are: 1. To find out if there is significant influence between Individual Characteristics on EmployeePerformance At the General Hospital of Brebes and 2. to determine how much influence Individual Characteristics on Employee Performance At the General Hospital of Brebes. This type of research is a case study at the General Hospital of Brebes, In a hypothesis test tool Spearmans rank and t test. Results obtained by analysis:correlation coefficient significance test results at 5% percent confidence level and degrees of freedom (85-2) obtained t table of 1.989 and on the calculation of t obtained at 2.2257 so t count> t table, then Ho is rejected and Ha received, meaning there is a significant correlation between individual characteristic of the employment of the employees performance, and the results of the calculation of the Spearman correlation coefficient of 0.9619, which means the proximity of the two variables is strong because the numbers one and positive approach. And his powerful this relationship can be seen from the performance of the employee (Y) on the determination coefficient of 0.558 or 55.80 percent.